2022
DOI: 10.1021/acs.iecr.2c00456
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Synthesis of C4 Compound with Low Carbon Emission from Acetaldehyde: Aldol Condensation Catalyzed by Regulable Acidic–Alkaline Al/Mg Sites of CuMgAlO

Abstract: Aldol condensation is an optimal method for carbon growth free from the thermo-cleavage technique of fossil resources with high carbon emissions. To further develop a catalyst with high activity and selectivity, a CuMgAl layered double oxide, named X/CuMgAlO, is successfully obtained after calcinating the MgAl hydrotalcite precursor doped with Cu 2+ . The resulting sample is applied as a catalyst in the self-condensation of acetaldehyde to crotonaldehyde. On the basis of the investigation of the reaction condi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…However, it is noticeable that the above catalysts have merely a single function of either a Lewis acidic or alkaline catalyst for aldol condensation, which usually renders it difficult to achieve high yields of the target products, as well. In contrast to conventional single-functional catalysts, polymetallic catalysts with multifunction have recently garnered considerable interest in the context of typical aldol condensation. In 2022, Yan et al reported a CuMgAlO layered double oxide catalyst and applied it in the preparation of crotonaldehyde by aldol condensation. The selectivity of crotonaldehyde was increased to 80.4% after doping with Cu, which is much higher than that catalyzed by the primary MgAlO oxide.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is noticeable that the above catalysts have merely a single function of either a Lewis acidic or alkaline catalyst for aldol condensation, which usually renders it difficult to achieve high yields of the target products, as well. In contrast to conventional single-functional catalysts, polymetallic catalysts with multifunction have recently garnered considerable interest in the context of typical aldol condensation. In 2022, Yan et al reported a CuMgAlO layered double oxide catalyst and applied it in the preparation of crotonaldehyde by aldol condensation. The selectivity of crotonaldehyde was increased to 80.4% after doping with Cu, which is much higher than that catalyzed by the primary MgAlO oxide.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to conventional single-functional catalysts, polymetallic catalysts with multifunction have recently garnered considerable interest in the context of typical aldol condensation. 23−26 In 2022, Yan et al 27 reported a CuMgAlO layered double oxide catalyst and applied it in the preparation of crotonaldehyde by aldol condensation. The selectivity of crotonaldehyde was increased to 80.4% after doping with Cu, which is much higher than that catalyzed by the primary MgAlO oxide.…”
Section: Introductionmentioning
confidence: 99%